Virtual Enterprise integration management based on a Meta-enterprise - A PMBoK approach - Ferreira, L. (2017)
A Virtual Enterprise (VE) can be viewed as a project, with a lifecycle corresponding to the period between its creation and integration of the constituting elements until its dissolution, comprehending its operation and including its reconfigurations. The authors propose that the VE lifecycle is aligned and can be managed using the frameworks provided by several bodies of knowledge, such as the PMBoK Guide. In this paper the authors propose an alignment referential between the Project Management phases defined by PMBoK and management processes during the VE lifecycle.